An electronic ceramic brazing process

CN122916708APending Publication Date: 2026-10-16XINXING ELECTRONIC CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611149510.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

①润湿性差与界面结合力弱:陶瓷表面与金属钎料的化学相容性和润湿性差

Benefits of technology

本发明提供了一种电子陶瓷钎焊工艺,通过在电子陶瓷表面激光熔覆特定成分的过渡层,利用过渡层与焊膏良好的冶金相容性,结合硼与钼、铁反应原位生成弥散分布的硼化物硬质相以及铬的晶格替换强化,不仅显著提升了过渡层的硬度、耐磨性和抗氧化性,而且铬还能与钎料中的活性钛形成金属间化合物,促进焊膏的润湿铺展,碳化钛的添加有效调节了过渡层的热膨胀系数,使其在陶瓷基体与金属钎料层之间形成热力学缓冲带,稀土氧化物的晶界钉扎与净化作用进一步细化了熔覆组织,提高了致密性和韧性,从源头抑制微裂纹的萌生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916708A_ABST
    Figure CN122916708A_ABST
Patent Text Reader

Abstract

The present application relates to the field of ceramic metallization process, specifically to a kind of electronic ceramic brazing process, comprising: preparing transition layer on the surface of electronic ceramic;Preparation of porous aluminum borate whisker-containing solder paste;By screen printing technology, solder paste is coated on the transition layer on the surface of electronic ceramic, and metal sheet is stacked on it to obtain brazing piece, and the brazing piece is sent into vacuum brazing furnace for vacuum brazing, the present application is designed by the double design of transition layer and porous whisker reinforced brazing seam, significantly reduces the residual stress of ceramic / metal interface, greatly improves the peel strength and cold thermal cycle resistance of joint, effectively solves the problems of poor wettability, large thermal stress and insufficient reliability in traditional electronic ceramic brazing process, and has important application value in the field of power electronic device packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic metallization processes, specifically to an electronic ceramic brazing process. Background Technology

[0002] As power electronics technology advances towards higher power density, higher integration, and higher operating temperatures, extremely stringent requirements are placed on the performance of packaging substrates. Electronic ceramic materials, such as alumina, aluminum nitride, and silicon nitride, have become core materials for high-power module packaging substrates due to their excellent electrical insulation, high thermal conductivity, and coefficient of thermal expansion that matches that of chip materials.

[0003] In practical applications, electronic ceramic substrates typically require reliable connections to metal heat sinks or electrodes, such as oxygen-free copper or Kovar alloys, to achieve electrical interconnection and heat dissipation in circuits. Brazing is one of the most important processes for connecting ceramics to metals. However, brazing ceramics to metals faces numerous technical challenges: ① Poor wettability and weak interfacial bonding: The ceramic surface and the metal brazing filler metal have poor chemical compatibility and wettability.

[0004] ② Thermal expansion coefficient mismatch: The thermal expansion coefficients of ceramics and metals differ significantly. During the thermal cycling process of brazing, cooling, and subsequent service, severe thermal stress is generated at the interface. This stress not only reduces the connection strength but, more seriously, can lead to warping and deformation of the ceramic substrate or even brittle fracture.

[0005] ③ Coarsening of the brazing seam structure and insufficient service reliability: Under long-term high and low temperature service environments, the creep resistance and fatigue life of the joint will be significantly reduced.

[0006] To overcome the above-mentioned defects, developing an electronic ceramic brazing process that can significantly reduce thermal stress at the ceramic / metal interface, improve interfacial bonding strength, and enhance the thermal stability of the brazing seam structure is of vital practical significance for improving the lifespan and reliability of power electronic devices. Summary of the Invention

[0007] Purpose of the invention: In view of the above-mentioned technical problems, the present invention proposes an electronic ceramic brazing process.

[0008] The technical solution adopted is as follows: An electronic ceramic brazing process includes the following steps: A transition layer is prepared on the surface of electronic ceramics; Preparation of solder paste containing porous aluminum borate whiskers; Solder paste is applied to the transition layer on the surface of electronic ceramics using screen printing technology, and metal sheets are stacked on top to obtain a brazed part. The brazed part is then sent into a vacuum brazing furnace for vacuum brazing.

[0009] As a further improvement of the present invention, the transition layer is prepared by in-situ melting and solidification of metal-ceramic powder on the surface of electronic ceramics using laser cladding technology. Laser cladding technology can provide extremely high energy density and extremely fast cooling rate, which can not only achieve micro-metallurgical bonding between metal-ceramic powder and ceramic matrix, but also refine the grain size of the transition layer and reduce interface defects.

[0010] As a further improvement of the present invention, the metal-ceramic powder is made from the following raw materials by weight percentage: The composition consists of 45-50% molybdenum powder, 5-10% boron powder, 8-12% chromium powder, 4-6% titanium carbide, 1-3% rare earth oxides, and the balance being iron powder.

[0011] Furthermore, the rare earth oxide is any one or a combination of two or more of lanthanum oxide, cerium oxide, or yttrium oxide.

[0012] The mechanism behind the design of this transition layer composition lies in the following: Molybdenum and iron, as matrix elements, possess excellent high-temperature resistance and moderate coefficients of thermal expansion. Furthermore, iron exhibits good solid solution or metallurgical compatibility with silver and copper in the solder paste. Boron is added to react with molybdenum and iron during laser cladding to generate a hard boride phase (Mo2FeB2). These hard phases are dispersed throughout the transition layer, improving its wear resistance and strength while also serving as a nucleation core to refine the microstructure. Chromium replaces molybdenum and iron in the boride hard phase lattice, significantly enhancing the transition layer's oxidation and corrosion resistance. Moreover, chromium can form intermetallic compounds with titanium, which is beneficial for the wetting and spreading of AgCuTi solder paste. The addition of titanium carbide ceramic particles further modulates the overall coefficient of thermal expansion of the transition layer, creating a thermodynamic buffer zone between the ceramic matrix and the solder layer. The addition of trace amounts of rare earth oxides utilizes the pinning and purifying effect of rare earth elements at grain boundaries, which can refine the structure of the laser cladding layer, improve the density and toughness of the cladding layer, and prevent the generation of microcracks.

[0013] As a further improvement of the present invention, the method for preparing the porous aluminum borate whiskers is as follows: Aluminum hydroxide, boric acid, and potassium chloride are mixed and heat-treated at 1280-1380℃ for 5-10 hours. Then, the temperature is lowered to 1000-1100℃ and kept at that temperature for 1-3 hours under an ammonia atmosphere. The product is then cooled, washed with water, and dried.

[0014] Aluminum hydroxide and boric acid react at this temperature to form aluminum borate whiskers. The introduced ammonia gas, at high temperature, may react with residual aluminum hydroxide, aluminum oxide, or boric acid inside / on the surface of the whiskers, generating water vapor which escapes rapidly, leaving micropores / mesopores inside the whiskers. The reaction products' lattice mismatch with the aluminum borate matrix and their different coefficients of thermal expansion, along with differences in cooling shrinkage, also contribute to the formation of interfacial pores. High-temperature ammonia gas has a slight etching effect on the whisker surface, further expanding the surface pore structure. Through the combined effects of these three mechanisms, porous aluminum borate whiskers are prepared.

[0015] The porous aluminum borate whiskers prepared in this invention possess unique physical and chemical properties: First, aluminum borate whiskers have a low coefficient of thermal expansion and exhibit anisotropy. The introduction of a porous structure further reduces their apparent elastic modulus, giving them a certain degree of elastic / plastic deformation capability under stress, which can effectively absorb strain energy caused by the thermal expansion mismatch between ceramics and metals.

[0016] Second, the pinning effect of the porous structure. The surface micropores and internal channels formed by ammonia etching allow AgCuTi solder paste to penetrate into the micropores of the whiskers during the brazing process through capillary action. After cooling, these form countless microscopic mechanical latches and pinning points, which greatly enhance the interfacial bonding strength between the whiskers and the solder matrix, preventing the whiskers from being pulled out or peeled off under stress. In addition, the micropore / mesopore structure may also help the brazed joint resist thermal cycling.

[0017] Third, the synergistic effect of active reactions. The surface of aluminum borate whiskers contains Al-O and BO active groups, which may react with the active element titanium in AgCuTi solder paste under high temperature and vacuum conditions, improving the wetting and chemical bonding ability of the solder paste. However, due to the buffering effect of the porous structure, the reaction will not cause violent damage to the whisker body.

[0018] Furthermore, the amount of potassium chloride used is 50-80% of the total mass of aluminum hydroxide and boric acid.

[0019] Potassium chloride melts at this temperature, acting as a molten salt flux to lower the reaction activation energy and provide a liquid-phase reaction environment. It also inhibits particle agglomeration, guides product growth along a one-dimensional direction to form aluminum borate whiskers, and the molten potassium chloride fills the spaces between whiskers and within whisker defects, reserving space for subsequent pore formation.

[0020] As a further improvement of the present invention, the solder paste is composed of AgCuTi metal powder, porous aluminum borate whiskers and organic carrier in a mass ratio of 8-9:0.1-0.5:1-2.

[0021] Furthermore, the AgCuTi metal powder is a commercially available active solder powder, preferably composed of Ag-28Cu-4Ti (mass percentage), with a powder particle size of 300-500 mesh.

[0022] Furthermore, the organic carrier is formulated from the following components in a certain proportion to adjust the viscosity and thixotropy of the solder paste to suit the screen printing process: terpineol (main solvent), diethylene glycol butyl ether (auxiliary solvent / film-forming aid), ethyl cellulose (thickener / binder), polyethylene glycol (plasticizer), hydrogenated castor oil (thixotropic agent), and stearic acid (dispersant / stabilizer).

[0023] As a further improvement of the present invention, the temperature rise parameters for the vacuum brazing step are as follows: Phase 1: Heat to 300-400°C within 20-40 minutes and hold for 10-20 minutes. The main purpose of this phase is to allow the organic carrier in the solder paste to completely volatilize and thermally decompose, preventing residual carbides from contaminating the solder joints. The heating rate should be controlled within a moderate range to prevent the excessive volatilization of organic matter from causing a loose solder paste layer or splattering.

[0024] The second stage involves heating to 600-700°C within 30-60 minutes and holding at that temperature for 10-20 minutes. This stage aims to pre-sinter the solder powder particles, expel residual gases between the particles, and allow the active element titanium in the solder to diffuse towards the interface, preparing for the wetting reaction with the transition layer.

[0025] The third stage involves rapidly heating to 880-900°C within 10-20 minutes and holding at that temperature for 5-10 minutes. This is the core stage for the melting, spreading, filling, and interfacial reaction of the brazing filler metal. It ensures sufficient isothermal solidification and interfacial reaction while preventing excessive erosion of the transition layer by the active element titanium. Excessive holding time will form coarse intermetallic compounds, deteriorating the joint performance.

[0026] As a further improvement of this invention, during the vacuum brazing process, a specially designed graphite jig or heat-resistant steel jig is used to apply an axial pressure of 0.5-2.0 MPa to the brazing workpiece. Applying axial pressure helps the liquid brazing filler metal to obtain additional extrusion pressure beyond capillary action, further filling the microscopic depressions on the surface of the transition layer and the internal pores of the porous whiskers, thus enhancing interfacial contact. Simultaneously, appropriate pressure can counteract some of the warping deformation tendency caused by thermal expansion mismatch, ensuring the flatness of the substrate after brazing.

[0027] The beneficial effects of this invention are: This invention provides an electronic ceramic brazing process. By laser cladding a transition layer of specific composition onto the surface of the electronic ceramic, and utilizing the good metallurgical compatibility between the transition layer and the solder paste, combined with the in-situ generation of dispersed boride hard phases by the reaction of boron with molybdenum and iron, and the lattice substitution strengthening of chromium, the hardness, wear resistance, and oxidation resistance of the transition layer are significantly improved. Moreover, chromium can form intermetallic compounds with active titanium in the solder, promoting the wetting and spreading of the solder paste. The addition of titanium carbide effectively regulates the thermal expansion coefficient of the transition layer, forming a thermodynamic buffer zone between the ceramic matrix and the metal solder layer. The grain boundary pinning and purification effect of rare earth oxides further refines the cladding structure, improves density and toughness, and inhibits the initiation of microcracks from the source.

[0028] Simultaneously, this invention innovatively prepares porous aluminum borate whiskers and incorporates them into solder paste. During preparation, potassium chloride molten salt is used to guide the one-dimensional orientation of the whiskers through growth assistance. High-temperature etching under an ammonia atmosphere and a gas escape pore-forming mechanism create abundant micropores / mesopores on and within the whiskers. These porous structures draw in liquid solder paste through capillary action during brazing, and upon cooling, form numerous microscopic mechanical interlocks, significantly enhancing the interfacial bonding strength between the whiskers and the solder matrix. This prevents whisker pull-out or peeling under stress. Furthermore, the whiskers' low coefficient of thermal expansion and the low apparent elastic modulus imparted by the porous structure effectively absorb strain energy generated by the thermal expansion mismatch between ceramic and metal, providing stress buffering. In addition, the micropore / mesopore structure may also contribute to the brazed joint's resistance to thermal cycling.

[0029] By optimizing the ratio of AgCuTi powder, porous aluminum borate whiskers, and organic carrier in the solder paste, and employing a staged, precisely temperature-controlled vacuum brazing process, the invention ensures the gradual volatilization of the organic carrier, the pre-sintering and degassing of the solder powder, and the full spreading and appropriate reaction of the solder in the high-temperature section. The applied axial pressure further enhances the weld seam density and interfacial contact. This invention, through a dual design of a transition layer and porous whiskers reinforcing the weld seam, significantly reduces residual stress at the ceramic / metal interface, greatly improves the peel strength and resistance to thermal cycling of the joint, and effectively solves the problems of poor wettability, high thermal stress, and insufficient reliability in traditional electronic ceramic brazing processes. It has significant application value in the field of power electronic device packaging. Attached Figure Description

[0030] Figure 1 This is a SEM image of the porous aluminum borate whiskers prepared in Example 1 of the present invention. Detailed Implementation

[0031] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0032] Example 1: An electronic ceramic brazing process, comprising the following steps: S1: Use a 96% alumina ceramic substrate. Before use, ultrasonically clean the ceramic substrate sequentially in acetone, anhydrous ethanol, and deionized water for 15 minutes each to thoroughly remove surface oil and machining residues. Then dry for later use.

[0033] Oxygen-free copper sheets (purity ≥ 99.9%) were selected as the metal to be joined. The surface of the copper sheets was polished with 400#, 800# and 1200# metallographic sandpaper in sequence to remove the surface oxide scale. After polishing, the sheets were ultrasonically cleaned with acetone and anhydrous ethanol and then dried for later use.

[0034] S2: Weigh the following raw materials according to weight percentage: 48% molybdenum powder (99.9% purity, average particle size 5μm), 8% boron powder (99.5% purity, amorphous), 10% chromium powder (99.9% purity, average particle size 10μm), 5% titanium carbide powder (99.5% purity, average particle size 2μm), 2% lanthanum oxide powder (99.99% purity, average particle size 1μm), and the balance is iron powder (99.9% purity, average particle size 3μm). Place the weighed powders in a planetary ball mill, use anhydrous ethanol as a ball milling aid, the ball-to-material ratio is 10:1, the speed is 250 rpm, and the mixture is ball-milled for 6 hours. The mixed slurry is dried in a vacuum drying oven at 80°C for 8 hours, and then sieved to obtain uniformly dispersed metal-ceramic powder.

[0035] An alumina ceramic substrate was fixed on a laser processing platform. Using a coaxial powder-feeding laser cladding system, the prepared metal-ceramic powder was fed into the molten pool at a powder feeder rate of 1 g / min. The laser process parameters were set as follows: laser power 4000 W, spot diameter 3 mm, scanning speed 400 mm / min, and overlap rate 40%. The entire cladding process was carried out in an argon protective atmosphere. After cladding, the surface of the transition layer was gently sanded with sandpaper and wiped clean with alcohol. The thickness of the transition layer was measured to be approximately 20 μm.

[0036] S3: Aluminum hydroxide and boric acid were mixed in a molar ratio of 9:4, and then mixed with potassium chloride. The amount of potassium chloride was 65% of the total mass of aluminum hydroxide and boric acid. The mixture was placed in a tube furnace and heated to 1330℃ for 7 hours in an air atmosphere. Then, it was cooled to 1050℃, and the air in the tube furnace was replaced with ammonia. The furnace was then kept at this temperature for 2 hours under an ammonia atmosphere. After cooling, the product was removed, thoroughly washed with deionized water, and then vacuum dried to obtain porous aluminum borate whiskers. See the SEM image below. Figure 1 It can be seen that its surface has relatively uniformly distributed pores.

[0037] S4: In a flask equipped with a stirrer and reflux condenser, add the following components sequentially and mix well (by weight percentage): 15% diethylene glycol butyl ether, 5% ethyl cellulose, 5% polyethylene glycol (PEG-4000), 3% hydrogenated castor oil, 2% stearic acid, and the balance is terpineol. Heat to 80°C and stir continuously for 4 hours to form a transparent, viscous liquid. After cooling, seal and allow to stand to obtain the organic carrier. Weigh Ag-28Cu-4Ti alloy powder (300 mesh), porous aluminum borate whiskers, and the organic carrier according to a mass ratio of 8.5:0.2:1.3. Grind and mix the organic carrier and porous aluminum borate whiskers for 15 minutes. Then add the Ag-28Cu-4Ti alloy powder in batches and continue grinding and mixing for 30 minutes to ensure uniform dispersion of the three components to obtain AgCuTi solder paste.

[0038] S5: Using a 200-mesh stainless steel screen printing plate, place the alumina ceramic substrate on the printing table. Apply the prepared AgCuTi solder paste to one end of the screen. Using a polyurethane squeegee, print once at a 45° angle and a speed of 50 mm / s to evenly transfer the solder paste to the transition layer surface. The wet film thickness after printing is controlled at 80-100 μm. After printing, carefully lay the oxygen-free copper sheet flat on the solder paste layer and gently rotate and press it to form a sandwich-structured brazed part. Place the assembled brazed part into a specially made graphite jig. Apply an axial pressure of 1 MPa through the pressure mechanism at the top of the jig to send the brazed part into the vacuum brazing furnace. Close the furnace door, start the vacuum system, and wait for the vacuum degree inside the furnace to reach 5 × 10⁻⁶. -3 Pa, start the heating program, and strictly follow the following parameters for temperature control curve: heat up to 350℃ within 30 minutes, hold for 15 minutes, then heat up to 650℃ within 45 minutes, hold for 15 minutes, then heat up to 890℃ within 15 minutes, hold for 8 minutes, and finally turn off the heating program and let the furnace cool to room temperature.

[0039] Example 2: Basically the same as Example 1, except that the S3 operation is different.

[0040] S3: Mix aluminum hydroxide and boric acid in a molar ratio of 9:4, and then mix with potassium chloride. The amount of potassium chloride is 80% of the total mass of aluminum hydroxide and boric acid. Place the mixture in a tube furnace and heat it to 1280℃ for 10 hours in an air atmosphere. Then cool it down to 1000℃, replace the air in the tube furnace with ammonia, and then continue to hold it at the ammonia atmosphere for 3 hours. Cool and take out the product, wash it thoroughly with deionized water, and then vacuum dry it to obtain porous aluminum borate whiskers.

[0041] Example 3: Basically the same as Example 1, except that the S3 operation is different.

[0042] S3: Mix aluminum hydroxide and boric acid in a molar ratio of 9:4, and then mix with potassium chloride. The amount of potassium chloride is 50% of the total mass of aluminum hydroxide and boric acid. Place the mixture in a tube furnace and heat it to 1380℃ for 5 hours in an air atmosphere. Then cool it down to 1100℃, replace the air in the tube furnace with ammonia, and then continue to hold it at the ammonia atmosphere for 1 hour. Cool and take out the product, wash it thoroughly with deionized water, and then vacuum dry it to obtain porous aluminum borate whiskers.

[0043] Example 4: Basically the same as Example 1, except that the S5 operation is different.

[0044] S5: Using a 200-mesh stainless steel screen printing plate, place the alumina ceramic substrate on the printing table. Apply the prepared AgCuTi solder paste to one end of the screen. Using a polyurethane squeegee, print once at a 45° angle and a speed of 50 mm / s to evenly transfer the solder paste to the transition layer surface. The wet film thickness after printing is controlled at 80-100 μm. After printing, carefully lay the oxygen-free copper sheet flat on the solder paste layer and gently rotate and press it to form a sandwich-structured brazed part. Place the assembled brazed part into a specially made graphite jig. Apply an axial pressure of 1 MPa through the pressure mechanism at the top of the jig to send the brazed part into the vacuum brazing furnace. Close the furnace door, start the vacuum system, and wait for the vacuum degree inside the furnace to reach 5 × 10⁻⁶. -3 Pa, start the heating program, and strictly follow the following parameters for temperature control curve: heat up to 300℃ within 40 minutes, hold for 20 minutes, then heat up to 700℃ within 30 minutes, hold for 10 minutes, then heat up to 880℃ within 20 minutes, hold for 10 minutes, and finally turn off the heating program and let the furnace cool to room temperature.

[0045] Example 5: Basically the same as Example 1, except that the S5 operation is different.

[0046] S5: Using a 200-mesh stainless steel screen printing plate, place the alumina ceramic substrate on the printing table. Apply the prepared AgCuTi solder paste to one end of the screen. Using a polyurethane squeegee, print once at a 45° angle and a speed of 50 mm / s to evenly transfer the solder paste to the transition layer surface. The wet film thickness after printing is controlled at 80-100 μm. After printing, carefully lay the oxygen-free copper sheet flat on the solder paste layer and gently rotate and press it to form a sandwich-structured brazed part. Place the assembled brazed part into a specially made graphite jig. Apply an axial pressure of 1 MPa through the pressure mechanism at the top of the jig to send the brazed part into the vacuum brazing furnace. Close the furnace door, start the vacuum system, and wait for the vacuum degree inside the furnace to reach 5 × 10⁻⁶. -3 Pa, start the heating program, and strictly follow the following parameters for temperature control curve: heat up to 400℃ within 20 minutes, hold for 10 minutes, then heat up to 600℃ within 60 minutes, hold for 20 minutes, then heat up to 900℃ within 10 minutes, hold for 5 minutes, and finally turn off the heating program and let the furnace cool to room temperature.

[0047] Comparative Example 1 It is basically the same as Example 1, except that it does not contain a transition layer, that is, there is no S2 step.

[0048] Comparative Example 2 It is basically the same as Example 1, except that the metal ceramic powder does not contain chromium powder.

[0049] Comparative Example 3 It is basically the same as Example 1, except that the metal ceramic powder does not contain lanthanum oxide powder.

[0050] Comparative Example 4 It is basically the same as Example 1, except that the metal ceramic powder does not contain titanium carbide powder.

[0051] Comparative Example 5 The method is basically the same as in Example 1, except that commercially available aluminum borate whiskers (Lana White) are used instead of the self-made porous aluminum borate whiskers.

[0052] Comparative Example 6 It is basically the same as Example 1, except that ammonia is not introduced in S3.

[0053] S3: Mix alumina and boric acid in a molar ratio of 9:4, and then mix them with potassium chloride. The amount of potassium chloride is 65% of the total mass of aluminum hydroxide and boric acid. Place the mixture in a tube furnace and heat it to 1330°C for 7 hours in an air atmosphere. Then cool it down to 1050°C and continue to heat it in an air atmosphere for 2 hours. After cooling, take out the product, wash it thoroughly with deionized water, and then vacuum dry it.

[0054] Performance testing: To verify the technical effects of the present invention, performance tests were conducted on the samples obtained in each embodiment and comparative example: ① Peel strength test The peel strength of the copper sheet was tested according to the IPC-TM-650 test method. A universal testing machine was used for the test, with a peel speed of 0.5 mm / min. Five samples were selected for each group, and the average value was taken.

[0055] ② Thermal cycling reliability test The sample was placed in a thermal shock test chamber. The temperature cycling range was set to -40℃ to 120℃, the high and low temperature transition time was less than 180s, and each high and low temperature was held for 15min as one cycle. The peel strength retention rate was tested after 100 cycles.

[0056] Table 1:

[0057] As shown in Table 1 above, the brazing process provided by the present invention can greatly improve the bonding strength between electronic ceramics and metals, and improve the lifespan and reliability of electronic devices.

[0058] The comparison between Example 1 and Comparative Example 1 shows that the introduction of the transition layer plays a positive role in improving the bonding performance between electronic ceramics and metals.

[0059] The comparison between Example 1 and Comparative Examples 2-4 shows that the introduction of chromium powder, lanthanum oxide powder and titanium carbide powder in the transition layer also plays a positive role in improving the bonding performance between electronic ceramics and metals.

[0060] The comparison between Example 1 and Comparative Example 5 shows that, compared with commercially available aluminum borate whiskers, adding self-made porous aluminum borate whiskers to solder paste can better improve the bonding performance between electronic ceramics and metals.

[0061] A comparison between Example 1 and Comparative Example 6 shows that without the introduction of ammonia gas in S3, a porous structure cannot be formed on the surface and / or inside of the aluminum borate whiskers, resulting in a decrease in the bonding performance between the electronic ceramic and the metal in Comparative Example 6.

[0062] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electronic ceramic brazing process, characterized in that, include: A transition layer is prepared on the surface of electronic ceramics; Preparation of solder paste containing porous aluminum borate whiskers; Solder paste is applied to the transition layer on the surface of electronic ceramics using screen printing technology, and metal sheets are stacked on top to obtain a brazed part. The brazed part is then sent into a vacuum brazing furnace for vacuum brazing.

2. The electronic ceramic brazing process as described in claim 1, characterized in that, The transition layer is made of metal-ceramic powder by laser cladding.

3. The electronic ceramic brazing process as described in claim 2, characterized in that, The cermet powder is made from the following raw materials by weight percentage: The composition consists of 45-50% molybdenum powder, 5-10% boron powder, 8-12% chromium powder, 4-6% titanium carbide, 1-3% rare earth oxides, and the balance being iron powder.

4. The electronic ceramic brazing process as described in claim 3, characterized in that, The rare earth oxide is any one or a combination of two or more of lanthanum oxide, cerium oxide, or yttrium oxide.

5. The electronic ceramic brazing process as described in claim 1, characterized in that, The method for preparing the porous aluminum borate whiskers is as follows: Aluminum hydroxide, boric acid, and potassium chloride are mixed and heat-treated at 1280-1380℃ for 5-10 hours. Then, the temperature is lowered to 1000-1100℃ and kept at that temperature for 1-3 hours under an ammonia atmosphere. The product is then cooled, washed with water, and dried.

6. The electronic ceramic brazing process as described in claim 5, characterized in that, The amount of potassium chloride used is 50-80% of the total mass of aluminum hydroxide and boric acid.

7. The electronic ceramic brazing process as described in claim 1, characterized in that, The solder paste is composed of AgCuTi metal powder, porous aluminum borate whiskers, and an organic carrier in a mass ratio of 8-9:0.1-0.5:1-2.

8. The electronic ceramic brazing process as described in claim 7, characterized in that, The organic carrier is composed of terpineol, diethylene glycol butyl ether, ethyl cellulose, polyethylene glycol, hydrogenated castor oil, and stearic acid.

9. The electronic ceramic brazing process as described in claim 1, characterized in that, The parameters for vacuum brazing are as follows: Increase the temperature to 300-400℃ within 20-40 minutes, hold for 10-20 minutes, then increase the temperature to 600-700℃ within 30-60 minutes, hold for 10-20 minutes, then increase the temperature to 880-900℃ within 10-20 minutes, and hold for 5-10 minutes.

10. The electronic ceramic brazing process as described in claim 1, characterized in that, During vacuum brazing, a fixture is used to apply an axial pressure of 0.5-2.0 MPa to the workpiece.